Geographic Information System and its Use in Capture Fisheries - Tangke, Umar (Agrikan Jurnal Agribisnis Perikanan, 2023)
Challenges in the development of fisheries business in Indonesia are the weak fisheries data and information system that affects its accuracy and timeliness.timeliness. These weaknesses can lead to wrong planning that ultimately leads to business failure.ultimately leading to business failure. As an archipelagic country, Indonesia should have a Fisheries Information System. The system This information system will provide great benefits, especially in utilization of fisheries resources in a sustainable manner. Information system has three main elements, namely data that provides information, procedures that tell users how to operate the information system, and procedures that tell users how to operate the information system. procedures that tell users how to operate the information system, and people who create products, solve problems, make decisions, and use the information system, and use the information system. The integration of the various elements of fisheries information system ynergistically will provide or create conditions conducive to the utilization of fisheries resources. conditions conducive to the wise and prudent utilization of fisheries resources by guiding the aspects of fisheries information system. utilization of fisheries resources wisely by guided by conservation aspects.